Efficacy of Quadratus Lumborum Block Compared to Paravertebral Block on Pediatric Patients Undergoing Abdominal Surgery - Sudiantara, Putu Herdita; Widnyana, I Made Gede; Putra, Kadek Agus Heryana; Kurniyanta, I Putu; Senapathi, Tjokorda Gde Agung (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif (PERDATIN) / The Indonesian Society of Anesthesiology and Intensive Care (INSAIC), 2024)
Background: Abdominal surgery is a major procedure associated with severe postoperative pain in pediatric patients. Quadratus lumborum block (QLB) is considered an effective pain control in such cases. Paraverterbral block (PVB) is another option for postoperative pain management. The aim of this study was to compare the effectiveness of quadratus lumborum block with paravertebral block. Methods: This single-blind randomized controlled trial included 22 pediatric patients who underwent abdominal surgery at Sanglah Hospital, Denpasar between August – October 2022. Research subjects were divided into 2 treatment groups; group A consisted of general anesthesia combined with quadratus lumborum block and group B consisted of general anesthesia combined with paravertebral block. Duration of analgesia was recorded based on the time to analgesic rescue, FLACC pain scale at 0, 2, 4, 6, 12 and 24 hours and total opioid consumption 24 hours after surgery. Statistical analyses were performed using SPSS. Results: Eleven patients received QLB and PVB respectively. There was a significant difference in mean analgesia duration of 1287 ± 129.69 minutes compared to 750 ± 122.22 minutes (p < 0.001) (CI 95%: 425.18 – 649.36), median FLACC pain scale at 12 (1 (IQR 2) vs 4 (IQR 1)) and 24 hours postoperative (1 (IQR 2) vs 3 (IQR 1)) between QLB and PVB (p < 0.001 and p < 0.007). Mean 24-hour postoperative opioid consumption was significantly lower in the QLB compared to the PVB. Conclusion: QLB has better effectiveness than PVB in pediatrics undergoing abdominal surgery.